Strategi Pengembangan Produksi Karak Kaliang 88 (Studi Kasus pada Usaha Rumah Tangga Suka Maju di Banda Balantai Kecamatan Tanjung Harapan Kota Solok) - Mahmud, Mahmud; Helmayuni, Helmayuni; Nelvi, Yusmi; Roza, Helvita (Jurusan PIPS FKIP UMMY Solok, 2022)
The research aims to find out the strategies that must be carried out by the Karak Kaliang 88 Suka Maju household industry in running its business. The data analysis method used is quantitative and SWOT analysis. Based on the results of the analysis of the Karak Kaliang 88 Suka Maju household business, Tanjung Harapan District, Solok City, receipt of Rp. 906,750,000/year are obtained, revenues are Rp. 606,360,326/year, and profits are Rp. 602,065,730/year with a B/C Ratio of 2.00/year. Based on the SWOT analysis, it shows that the strategy used is S-O, namely using well-known brands and products that continuously develop the market. In addition, product quality improvement is also carried out.